(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
There is a saying, ’People speak with different tone of same vernacular language after the distance of every 15 villages’. Unity among diverse cultures, traditions and communities is the unique feature of India. The variety of costumes, festivals, art and craft keep people fascinated. Similarly it is also true in the case of handmade embroidery. Embroidery in India is different in different regions and states. The researchers can identify the origins of an embroidered piece of fabric simply by the style, colors, fabric and stitched used. Embroideries of Sindh, Kutch and Kathiawar are very popular among many types of embroidery in India.